Sport and exercise psychology in 2050 - Raab, M. (German Journal of Exercise and Sport Research, 2017)
Sport and exercise psychology by definition describes, explains and predicts human behaviour. Yet exact predictions of human behaviour are more the exception than the rule and thus it is no wonder that sport and exercise psychologists are not able to predict very well who will be a talent or win a gold medal in 10 years. In the same vein, it is somewhat easier to describe scientific endeavours in hindsight or by analysis of the current state of affairs than to predict what a discipline will be like in, say, 2050. Other disciplines that face similar levels of complexity have, however, tested their models on (near) future events, such as the mathematical prediction of president elections, climate change or which team will win the next soccer World Cup. Some disciplines have even tried to forecast what will be in 2050, for instance, predicting that soccer-playing robots will win an official soccer game against humankind. This opinion statement about sport and exercise psychology starts with a description of the current state of affairs in our field, followed by a prediction of sport and exercise psychology activities and potential successes in 2050, Thus, providing a platform for discussion of our mission as well as goal setting for the coming years.